Rapid determination of the tumour stroma ratio in squamous cell carcinomas with desorption electrospray ionization mass spectrometry (DESI-MS): a proof-of-concept demonstration. Issue 17 (11th August 2017) - Woolman, Michael; Tata, Alessandra; Dara, Delaram; Meens, Jalna; D'Arcangelo, Elisa; Perez, Consuelo J.; Saiyara Prova, Shamina; Bluemke, Emma; Ginsberg, Howard J.; Ifa, Demian; McGuigan, Alison; Ailles, Laurie; et al.
Abstract : Prognostic tumour stroma ratios from DESI-MS. Abstract : Squamous cell carcinomas constitute a major class of head & neck cancers, where the tumour stroma ratio (TSR) carries prognostic information. Patients affected by stroma-rich tumours exhibit a poor prognosis and a higher chance of relapse. As such, there is a need for a technology platform that allows rapid determination of the tumour stroma ratio. In this work, we provide a proof-of-principle demonstration that Desorption Electrospray Ionization Mass Spectrometry (DESI-MS) can be used to determine tumour stroma ratios. Slices from three independent mouse xenograft tumours from the human FaDu cell line were subjected to DESI-MS imaging, staining and detailed analysis using digital pathology methods. Using multivariate statistical methods we compared the MS profiles with those of isolated stromal cells. We found that m / z 773.53 [PG(18:1)(18:1) − H] −, m / z 835.53 [PI(34:1) − H] − and m / z 863.56 [PI(18:1)(18:0) − H] − are biomarker ions that can distinguish FaDu cancer from cancer associated fibroblast (CAF) cells. A comparison with DESI-MS analysis of controlled mixtures of the CAF and FaDu cells showed that the abundance of the biomarker ions above can be used to determine, with an error margin of close to 5% compared with quantitative pathology estimates, TSR values. This proof-of-principle demonstration is encouraging and must be further validated using human samples and a larger sample base. At maturity, DESI-MS thus may become a stand-alone molecular pathology tool providing an alternative rapid cancer assessment without the need for time-consuming staining and microscopy methods, potentially further conserving human resources.